Peran Pemerintah Indonesia dalam Menangani Pengungsi Rohingya di Wilayah Perbatasan Riau Tahun 2022-2024 - Indi Fricylia H; M. Arsy Ash Shiddiqy (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
Rohingya refugees are an ethnic minority group from Myanmar seeking protection from persecution and violence. Their presence in the border region of Riau Province, Indonesia, poses humanitarian, security, and diplomatic challenges that require humane and internationally standard responses. This study aims to analyze the role of the Indonesian government, particularly the Riau Provincial Government, in handling Rohingya refugees from 2022 to 2024. The methodology used is a qualitative approach with a phenomenological method. Primary data collection was conducted through interviews and observations, while secondary data came from official documents and journals related to the Rohingya refugee issue. Data analysis uses condensation, presentation, and conclusion-drawing techniques. This study finds that the role of the Indonesian government includes multilateral coordination, the implementation of humanitarian policies, human rights protection, health services, and refugee security, in accordance with international instruments and principles. In addition to multilateral cooperation, the role of non-state actors is also important in maintaining human security and meeting the needs of Rohingya refugees. This study contributes to understanding the roles of the government and related actors, while also serving as an important reference for finding humane and constructive solutions to the Rohingya refugee issue on the Riau border.